If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 5(x + -2) + -4x + -8 Reorder the terms: 10 = 5(-2 + x) + -4x + -8 10 = (-2 * 5 + x * 5) + -4x + -8 10 = (-10 + 5x) + -4x + -8 Reorder the terms: 10 = -10 + -8 + 5x + -4x Combine like terms: -10 + -8 = -18 10 = -18 + 5x + -4x Combine like terms: 5x + -4x = 1x 10 = -18 + 1x Solving 10 = -18 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -1x = -18 + 1x + -1x Combine like terms: 1x + -1x = 0 10 + -1x = -18 + 0 10 + -1x = -18 Add '-10' to each side of the equation. 10 + -10 + -1x = -18 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -18 + -10 -1x = -18 + -10 Combine like terms: -18 + -10 = -28 -1x = -28 Divide each side by '-1'. x = 28 Simplifying x = 28
| -6(x-1)+8=-5(x+7) | | -3(t-5)+5t=8t-3 | | 5p^2=-7p-2 | | 0.2(x+7)=8 | | 5(2p+3)=50 | | 11x-3x=4(7)-4 | | X^2+8x-768=0 | | 2x+3=2.5x+1 | | 22n+3p-15n= | | ((x+1)/(2x-5))=3/4 | | -6-c=2 | | 2y+3x-4x+2y= | | (x+1)/(2x-5)=3/4 | | e^9x+7=6 | | 11*6=23.60 | | x+14.3=42 | | 3x+8=2+48 | | x(x+2)=28 | | 4*(x*x)-8=56 | | -2(-15x-1)-5=6(5x-4)+30 | | -2(-15z-1)-5=6(5z-4)+30 | | x*x=98 | | 9n-3p+3p= | | x*x*x=98 | | 6y-8y+y= | | 2x-7y=-28 | | 15/7*y=3 | | 4x+30=12x-50 | | 1-4x=7-x | | 1-4x=7-x | | 26=22-4(3-4w) | | 9x-9y=0 |